ANALISIS KINERJA KEUANGAN PADA PT. HERO SUPERMARKET Tbk - -, Rimah Melati (EKONOMIA, 2015)
The problem in this study is the first that Is financial performance such as profit margin in PT Hero Supermarket Tbk years 2008-2012 are reviewed by Du Pont System has met industry standards. Secondly, Is the financial performance of a turnover of operating assets in PT Hero Supermarket Tbk years 2008-2012 are reviewed by Du Pont System has met industry standards. And third, Is the financial performance in the form of return on investment in PT Hero Supermarket Tbk years 2008-2012 are reviewed by Du Pont System has met industry standards.The purpose of this study is to determine the financial performance of profit margin,turnover of operating assets, and return on investment in PT Hero Supermarket Tbk years 2008-2012 are reviewed by Du Pont System has met industry standards. Basic theory used is Management Accounting using the Return On Investment analysis tools to approach Du Pont System.Based on the analysis and discussion of the conclusions of this study are first that profit margins from the year 2008-2012 has always been below the industry standard. With an average profit margin of only 2.45%, it will show inefficiencies company in suppressing existing costs to achieve optimal profit because it is still far from the standard profit margin of 20% Kasmir, the hypothesis is accepted. Secondly, Turnover of operating assets (TOA) from 2008-2012 has always been above the standard TOA Kasmir by 2 times. And with the average turnover of operating assets at 2.40 times the rate of turnover of company assets already very good because it exceeds the industry standard, then the hypothesis is accepted. And third, Return on investment (ROI) from 2008-2012 always under standard ROI of 30% Kasmir. With an average ROI of only 5.93%, the financial performance of PT Hero Supermarket is categorized with poor performance because it can not reach the standard of the industry shows the inefficiency in utilizing the company's net profit on work done, not fully able to meet the investment capital from investors, then the hypothesis is accepted.Suggestion filed in connection with this study is that PT Hero Supermarket Tbk concerned about cost of goods sold and general and administrative expenses that are not too high so that the company can increase its business revenues and high operating profit each year. As for the next researcher who will conduct research related to the analysis of financial performance, should be able to use the method of residual income (RI) in addition to the return on investment (ROI). Due to the use of both methods, it will be known how the company's actual financial performance. Becaause both method sare comprehensive and complementary